(3ebOeI aj Yde GdMGShH h GdHQeLI HdZI HjSc dWdHI GdLGeYGJ (B/s - (3QMh, ZGRj GHQGgjes; (3GdUHGZ, YeGO YHO GdhgGH s ((3YeGf(B: s (3OGQ RgQGf ddfTQ hGdJhRjY(B, s, 2011)
(3GdMSGH h GdMGShH, GdHQeLI h GYOGO GdHQGeL, CSGSjGJ GdHQeLI HdZI HjSc, GdeNWWGJ GdGfSGfjI h GONGd GdHjGfGJ Ch Gdbje ddeJZjQGJ, YHGQGJ GdGNQGL, YHGQGJ GdJcQGQ h YHGQGJ GNQi HdZI HjSc, GdQhJjfGJ GdaQYjI h GSJNOGe GdhXGFa GdebOeI eSHbG HGSJNOGe (Bdef(3h (BGo sub (3edaGJ GdHjGfGJ h fXGe GdJTZjd h CNjQG CSFdI h CeKdI YGeIs
Keywords: (3GdEYdGe GdCdjs; (3GdHQeLjGJs; (3GdMGShHs; (3Yde GdMGShHs